Komparasi Model Pembelajaran Teaching Factory dengan Project Based Learning Terhadap Keaktifan dan Hasil Belajar - Oktafia, Novi Arnita; Kholisho, Yosi Nur (Universitas Hamzanwadi, 2019)
This study aimed to determine the comparison of Teaching Factory (TEFA) learning models with Project Based Learning (PjBL) on the active and learning outcomes of class XI Multimedia students in 2D and 3D Animation learning at Vocational High School of Janapria in 2019/2020 Academic Year. This type of research is quantitative with the Quasi Experimental method. The population of this study was all 60 students of class XI Multimedia 1 Janapria Vocational High School, with samples using cluster sampling techniques. Class XI Multimedia-A as an experimental class I with 30 students while class XI Multimedia-B as an experimental class II with a total of 30 students. The research design used was Nonequivalent Control Group Design. Data collection used observation and tests. Data analysis used Paired Sample T Test. The results showed that 1) there was no difference in student learning activeness using the TEFA learning model with PjBL (with a significance value Ï> 0,05),Â 2) there was no difference in student learning outcomes using the TEFA learning model with PjBL (with a significance value Ï> 0,05). Therefore, there is no difference in the activeness and learning outcomes of students using the TEFA learning model with PjBL in students class XI Multimedia of 2D and 3D Animation learning at Vocational High School of Â 1 Janapria 2019/2020 Academic Year.